Effect of Hybrid Gain Medium and Four Wave Mixing in Multiwavelength Fiber Laser - Sulaiman A.H.; Ramachandran D.; Abdullah F.; Ismail A.; Jamaludin M.Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Fiber lasers; Extinction ratios; Gain medium; Highly nonlinear fibers; Hybrid gain mediums; Lasing lines; Multi wavelength fiber laser; Four wave mixing